2017
DOI: 10.1177/0193945916687994
|View full text |Cite
|
Sign up to set email alerts
|

Parental Feeding Behaviors and Weight-Related Concerns in Children With Special Needs

Abstract: Parental feeding behaviors and concern about child weight are associated with obesity among youth who are typically developing. Little is known about this relationship among parents of youth with special needs, despite these children having higher obesity risk. This study used an online survey to explore associations among parental feeding behaviors, parent weight concerns, demographics, and child weight status in a sample of 356 parents of children diagnosed with autism spectrum disorder, spina bifida, and Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 32 publications
1
29
1
1
Order By: Relevance
“…In the current study, only 3 subscales of the seven subscales from the CFQ were used to measure parent-child feeding relationship. These subscales were chosen based on applicability to the study aims, previously documented validity, internal consistency and to decrease the burden on the study participants [20].…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, only 3 subscales of the seven subscales from the CFQ were used to measure parent-child feeding relationship. These subscales were chosen based on applicability to the study aims, previously documented validity, internal consistency and to decrease the burden on the study participants [20].…”
Section: Methodsmentioning
confidence: 99%
“…Children who experience delays in growth (e.g., premature infants) may also require specialized feeding approaches, and feeding can be a source of anxiety for parents in such cases. Parents of children with developmental delays have been found to use more controlling feeding practices [22] and may also experience more mealtime challenges [23].…”
Section: Child Factorsmentioning
confidence: 99%
“…Recent increases in the rates of childhood obesity and associated health risks have drawn the attention of scientists [4,[7][8][9]. Ek et al showed that the occurrence of overweight and obesity was closely correlated with both feeding practices and eating behaviors [10].…”
Section: Introductionmentioning
confidence: 99%